LMP1 and EBNA2 constitute a minimal set of EBV genes for transformation of human B cells - Zhang, Jingwei; Sommermann, Thomas; Li, Xun; Gieselmann, Lutz; de la Rosa, Kathrin; Stecklum, Maria; Klein, Florian; Kocks, Christine; Rajewsky, Klaus (Frontiers in Immunology, 2023)
Introduction Epstein-Barr virus (EBV) infection in humans is associated with a wide range of diseases including malignancies of different origins, most prominently B cells. Several EBV latent genes are thought to act together in B cell immortalization, but a minimal set of EBV genes sufficient for transformation remains to be identified. Methods Here, we addressed this question by transducing human peripheral B cells from EBV-negative donors with retrovirus expressing the latent EBV genes encoding Latent Membrane Protein (LMP) 1 and 2A and Epstein-Barr Nuclear Antigen (EBNA) 2. Results LMP1 together with EBNA2, but not LMP1 alone or in combination with LMP2A was able to transform human primary B cells. LMP1/EBNA2-immortalized cell lines shared surface markers with EBV-transformed lymphoblastoid cell lines (LCLs). They showed sustained growth for more than 60 days, albeit at a lower growth rate than EBV-transformed LCLs. LMP1/EBNA2-immortalized cell lines generated tumors when transplanted subcutaneously into severely immunodeficient NOG mice. Conclusion Our results identify a minimal set of EBV proteins sufficient for B cell transformation.